Production of cocoa butter alternatives from blending bambangan kernel fat stearin and palm stearin for potential applications - Norazlina Mohammad Ridhwan; Hasmadi Mamat; Jahurul Haque Akanda (Springer Nature, 2024)
This work aimed to explore the composition, thermal characteristics, and morphological properties of binary blends composed of bambangan kernel fat stearin and palm stearin. Various attributes, including the fatty acid composition, triglyceride profile, solid fat content, and crystal microstructure, were assessed through gas chromatography, high-performance liquid chromatography, pulsed nuclear magnetic resonance, and polarization microscopy. Five binary mixtures were prepared using bambangan kernel fat stearin and palm stearin in varying ratios (g/100 g), with palm stearin content incrementally increasing by 5%. Among these blends, SS5, comprising 70% bambangan kernel fat stearin and 30% palm stearin, demonstrated properties on par with cocoa butter. It contained 21.73% palmitic, 38.92% stearic, and 31.12% oleic acids, along with 1,3-dipalmitate-2-oleate-glycerol, 1-palmitate-2-oleate-3-stearate-glycerol and 1,3-distearate-2-oleate-glycerol values of 10.35%, 10.95%, and 30.22%, respectively. When SS5 was blended with cocoa butter in proportions less than 40%, no tripalmitin was observed, and the thermal and morphological behaviour closely resembled that of cocoa butter. Therefore, SS5 (70:30, bambangan kernel fat stearin: palm stearin) presents a viable alternative due to its comparable properties and compatibility with cocoa butter.